2003
DOI: 10.1046/j.1523-1739.2003.02092.x
|View full text |Cite
|
Sign up to set email alerts
|

Limestone Quarries as Refuges for European Xerophilous Butterflies

Abstract: The large‐scale decline of traditionally managed early‐successional habitats caused by the joint effects of agricultural intensification and abandonment of marginal lands has resulted in a continent‐wide decline of xerophilous butterflies throughout Europe. The question is whether newly generated early‐successional sites of industrial origin may partially compensate for this habitat loss. We studied the butterfly assemblages of 21 limestone quarries in the region of Moravia, Czech Republic, within an important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
80
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(89 citation statements)
references
References 34 publications
(35 reference statements)
9
80
0
Order By: Relevance
“…Shapiro, 2002;Gaston et al, 2005). Many authors (Benes et al, 2003;Eyre et al, 2004;Saarinen et al, 2005;Tropek et al, 2010) showed that industrial and urban barrens may harbour insects depending on warm and dry microclimates. Wenzel et al (2006) detected losses of many xerophilous species from isolated xeric reserves embedded within intensively farmed rural matrix, attributing this to isolation and spillover effects from the farmland.…”
Section: Discussionmentioning
confidence: 99%
“…Shapiro, 2002;Gaston et al, 2005). Many authors (Benes et al, 2003;Eyre et al, 2004;Saarinen et al, 2005;Tropek et al, 2010) showed that industrial and urban barrens may harbour insects depending on warm and dry microclimates. Wenzel et al (2006) detected losses of many xerophilous species from isolated xeric reserves embedded within intensively farmed rural matrix, attributing this to isolation and spillover effects from the farmland.…”
Section: Discussionmentioning
confidence: 99%
“…abandonment of management, subsequent invasion of shrubs, high fragmentation due to agriculture intensification, habitat quality changes related to nutrient flow from surrounding farmland) is semi-natural calcareous grassland (Keymer & Leach, 1990). In fact, in central Europe, many calcareous grasslands are limited to small isolated patches, often located on hills or limestone outcrops (Beneš et al, 2003;Krauss et al, 2004;Wenzel et al, 2006). This habitat, however, is of leading conservation interest because of a high richness of plant and insect species (Van Swaay, 2002;Walis DeVries et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Man-made habitats, mostly quarries, embankments, banks, slopes of roads and ditches, as well as spoil tips, are convenient locations for grassland development and settlement of receding and rare species. Such processes were frequently observed both in Poland and in other countries [8,[61][62][63][64]. To a certain degree, the abundance of grassland sozophytes in anthropogenic habitats is also connected with the shrinkage of xerothermic grassland areas in Silesia [60] and, as a result, a high participation of grassland plants in the sozophyte group.…”
Section: The Role Of Anthropogenic Habitats For Regional Plant Covermentioning
confidence: 98%